Structural Design of Wind Turbine Blades with an Additively Manufactured Graded Lattice Core using Topology Optimisation. Issue 3 (1st May 2022) - Moss, A; Macquart, T; Panesar, A; Forrest, M; Greaves, P; Pirrera, A
Abstract: Conventional wind turbine blade manufacture relies on large, expensive moulds. Instead, using additive manufacturing to print the internal structure of blades, upon which it would be possible to lay composite plies, could significantly reduce manufacturing costs and, as one could "3D print" topologically optimal designs, improve structural efficiency. In general, topology optimisation integrates well with additive manufacturing. There are, however, two main challenges associated with the adoption of topology optimisation in wind blade design, i.e. accounting for: (i) the aeroelastic response of blades; and (ii) the variety of different materials that would be employed, in the composite laminates as well as the printed structure. To address these challenges, the present paper proposes a new multi-step design and optimisation framework relying on the combination of three software. First, a conventional aero-servo-elastic model is used to evaluate blade loads and displacements. Next, a topology optimisation software is used to optimise the blade laminates and core structure. Third, a lattice generator is used to convert the topological optimised "grey" design into an equivalent cellular design that can be printed using additive manufacturing. The full methodology of this design framework and an initial proof-of-concept topology optimisation solution are presented in this paper.